Applying models of scientific terms' surroundings in classification of scientific publications - Balys, Vaidas; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2004)
This paper considers a problem of classification of scientific publications wich is treated here as a problem of finding keywords. Keywords are determined by making use of statistical analysis of distribution of scientific terms. Models of scientific terms surroundings – so called identification clouds – are presented as well as results of experiments of their applicability for keywords detection.
Keywords: classification of publications; keywords; statistical models of terms distributions